2003
DOI: 10.1034/j.1600-065x.2003.00015.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the src‐family kinases, Lck and Fyn, on T cell differentiation, survival and activation

Abstract: The src-family kinases p56lck (Lck) and p59fyn (Fyn) are expressed in T cells and are among the first signaling molecules to be activated downstream of the T cell receptor (TCR). Evidence is emerging that although closely related, these signaling molecules have discrete functions during development, maintenance and activation of peripheral T cells. For example, during thymopoiesis Lck is uniquely able to provide all the signals required for pre-TCRbeta selection, although Fyn can substitute for a subset of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
143
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(151 citation statements)
references
References 91 publications
6
143
0
2
Order By: Relevance
“…2B), is consistent with the observed hyper-and hyporesponsive TCR signals seen in WEDGE and KO mice, respectively. It also concurs with the observation that higher Lck activity favors skewing of T cell differentiation toward CD4 ϩ T cells (28).…”
Section: Discussionsupporting
confidence: 75%
“…2B), is consistent with the observed hyper-and hyporesponsive TCR signals seen in WEDGE and KO mice, respectively. It also concurs with the observation that higher Lck activity favors skewing of T cell differentiation toward CD4 ϩ T cells (28).…”
Section: Discussionsupporting
confidence: 75%
“…Nonetheless, some functions have been identified that are unique to Lck. Examples are the positive selection of CD4 single-positive cells and the proliferation of T-cells in lymphopenic environments (46). The significant differences in SH2-SH3 linkage observed here may help to adapt Lck and Fyn to their specific surroundings and to achieve their functional differences.…”
Section: Sh3 and Sh2 Domain Communication By Ligand-bindingmentioning
confidence: 81%
“…The combinatorial interactions of these paired domains could contribute to differences in the binding specificities and the distinct substrate profile of these SFKs. Specific interactions for either Lck or Fyn have been reported (reviewed in Zamoyska et al, 2003). Distinct localization patterns also may contribute to the distinct specificities of these kinases.…”
Section: Lck and Fyn Domain Structure And Functionmentioning
confidence: 99%